The Kyoto Protocol: A Review and Perspectives - Christoph Böhringer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
International concern about climate change has led to the Kyoto Protocol, negotiated in 1997, which contains legally binding emission targets for industrialized countries to be achieved during the commitment period 2008-2012. While proponents of the Protocol celebrate it as a breakthrough in international climate policy, opponents criticize that its approach, namely setting targets and timetables for emission reductions, is seriously flawed. This paper provides a critical assessment of the Protocol?s potential performance and discusses amendments to foster its effectiveness and efficiency. It concludes that, even without any effective emission reductions in the initial commitment period, the ratification of Kyoto is important for the further policy process of climate protection. The Kyoto Protocol has established a flexible broad-based international mechanism that provides a valuable starting point for shaping efficient climate policies in the future.
Keywords: Q25; D61; H41; 330; climate policy; cost-benefit analysis; Kyoto Protocol; Klimaschutz; Umweltabkommen; Kosten-Nutzen-Analyse; Kritik; Welt